World resources, engineering solutions proceedings of the third joint conference of the American Society of Civil Engineers and the Institution of Civil Engineers, Harrogate, 30 September-3 October 1975 - Darwent, Thelma J. (Institution of Civil Engineers, 1976)
Topics covered in this book include human resources, energy resources and conservation of energy, metallic and non-metallic resources and other resources. Each paper concludes with a discussion of the subject, and Sir William Harris and Dr William M. Sangster provide closing addresses.